Correlation of Phenotype–Genotype and Protein Structure in RYR1-Related Myopathy - Chang, Xingzhi; Wei, Risheng; Wei, Cuijie; Liu, Jieyu; Qin, Lun; Yan, Hui; Ma, Yinan; Wang, Zhaoxia; Xiong, Hui (Frontiers in Neurology, 2022)
Introduction: Next generation sequencing results in an explosive identification of rare variants of RYR1, making the correlation between phenotype and genotype complicated. We analyzed data of 33 patients with RYR1-related myopathy, attempting to elucidate correlations between phenotype, genotype and protein structure of RyR1. Methods: Clinical, histopathologic and genetic data was evaluated, and variants were mapped to the cryo-EM RyR1 structure. The three-dimensional structure of variant on RyR1 was analyzed. Results: The clinical spectrum was highly variable regardless of the mode of inheritance. Recessive variations were associated with more severe feeding problems and respiratory insufficiency in infancy (P<0.05). Forty pathogenic and likely pathogenic variations were identified, 14 of them were novel. Missense was the most common variation type regardless of inheritance mode. Arginine (15/45) was the most frequently involved residue. All but one dominant variation clustered in Pore forming and pVSD domains, while recessive variations enriched in Bsol (7/25) and SPRYs (6/25) domains. Analysis of the spatial structure of variants showed that dominant variants may impact RyR1 mainly by breaking down hydrogen or electrovalent bonds (10/21); recessive variants located in different domains may impact the function of RyR1 through different pathways. Variants located in RyR1 coupling sites (PY1&2 and the outermost of Bsol) may cause the most severe clinical manifestation. Conclusion: Clinical diversity of RYR1-related myopathy was impacted by the inheritance mode, variation type and variant location. Dominant and recessive variants have different sensitive domains impacting the function of RyR1 through different pathways.